Kepribadian, Sosial Guru PAI, dan Pengaruhnya Terhadap Karakter Keagamaan Siswa - Undian Rukandi (UIN Fatmawati Sukarno Bengkulu, 2022)
The problem in this study is whether the personal competence and social competence of Islamic Education teachers together have an effect on the improvement of the religious character of the students of SMP Negeri 15 Lubuk lingau. This research is a quantitative research. The results showed that there was a significant influence between Teacher Personality Competence (X1) and Social Competence (X2) together on Student Religious Character (Y) SMP Negeri 15 Lubuklinggau. The effect of Teacher Personality Competence (X1) and Social Competence (X2) simultaneously on Student Religious Character (Y) based on the results of the “f” test in hypothesis 3 of 29,869, this means f count> f table (29,869> 3.28) and significance (0.000 <0.05). Based on the results of regression calculations, it can be seen that the coefficient of determination (adjusted R square) is 0.629. This means that 62% of the Religious Character of SMP Negeri 15 Lubuklinggau Students are influenced by the variables of Personality Competence (X1) and Social Competence (X2), while the remaining 38% of the Religious Character of SMP Negeri 15 Lubuklinggau Students is influenced by biological factors, namely factors that comes from within the person himself. This factor comes from heredity or congenital nature and the influence of heredity from one of the traits possessed by one of the two. Furthermore, environmental factors, in addition to heredity factors (endogenous factors) which are relatively constant in nature, milieu which consists of, among others, the environment, education, living conditions and situations and social conditions (all of which are exogenous factors) all have a major influence on character building. this includes the customs and regulations in force and the language that is moved.